2022
DOI: 10.1136/jnnp-2022-330091
|View full text |Cite
|
Sign up to set email alerts
|

Role of small acute hyperintense lesions in long-term progression of cerebral small vessel disease and clinical outcome: a 14-year follow-up study

Abstract: BackgroundSmall hyperintense lesions are found on diffusion-weighted imaging (DWI) in patients with sporadic small vessel disease (SVD). Their exact role in SVD progression remains unclear due to their asymptomatic and transient nature. The main objective is to investigate the role of DWI+lesions in the radiological progression of SVD and their relationship with clinical outcomes.MethodsParticipants with SVD were included from the Radboud University Nijmegen Diffusion tensor MRI Cohort. DWI+lesions were assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“… 21 Their clinical significance, and whether they relate to disease progression, remains to be fully determined although a recent report associated them with greater radiological progression of SVD and cognitive decline compared with patients without DWI + lesions. 22 It has also been suggested that WMH lesion volume may regress in some patients, and not only progress. 23 …”
Section: Insights From Brain Imagingmentioning
confidence: 99%
“… 21 Their clinical significance, and whether they relate to disease progression, remains to be fully determined although a recent report associated them with greater radiological progression of SVD and cognitive decline compared with patients without DWI + lesions. 22 It has also been suggested that WMH lesion volume may regress in some patients, and not only progress. 23 …”
Section: Insights From Brain Imagingmentioning
confidence: 99%
“…Small diffusion-weighted imaging-positive asymptomatic lesions on serial diffusion-weighted imaging are more common that previously observed and strongly associated with cognitive decline. 20 Ongoing international collaborative consortia are established to evaluate the impact of CSVD imaging markers on the risk of stroke and dementia across multiple populations. These have performed lesion-symptom mapping to identify strategic white matter hyperintensity locations for cognitive impairment 21 and established diffusion tensor imaging as a method to accurately predict dementia in CSVD.…”
Section: Csvd Is On the Risementioning
confidence: 99%